Evaluating the Topographical Factors Contributing to Landslide Occurrences in the Thuligad Watershed of Far-Western Province, Nepal - Bhandari, Bharat Prasad; Saud, Tekendra Bahadur; Ayer, Prakash Bahadur (Journal of Nepal Hydrogeological Association, 2025)
The Thuligad watershed in the Farwestern Province has been facing a substantial landslide challenge for a long time, especially during the monsoon season. The harsh topography, characterized by numerous steep slopes, is prevalent across the Thuligad watershed, resulting in a significant incidence of landslides across the area.This research aims to evaluate the impact of topographical factors to trigger landslide within the Thuligad watershed located in the Sudurpaschim province of Nepal. The work began with the use of satellite imagery and ArcGIS to develop a comprehensive spatial and temporal inventory map of landslides. The map illustrating the five topographical factors was generated utilizing a 12.5 m digital elevation model obtained from Alaska Satellite Fascility of United States Geological Survey. The dimensions of the pixel sizes pertaining to the subclasses of factors, as well as those associated with landslides within these subclasses, were ascertained. In a comparable manner, the quantity of landslides identified in relation to aspect, curvature, and slope was derived from both field observations and spatial analyst tool of ArcGIS. The dimensions of the landslide were determined through area measurement and subsequently correlated with the classification of the slope. A statistical index model was employed to ascertain the significant relationship between topographical factors and landslides. A notable positive correlation exists between slope and landslide density; however, the incidence and extent of landslides are greater within the slope range of 30 to 45 degrees. The density of landslides is markedly higher on slopes exceeding 60 degrees. The concave slope with a southern aspect exhibits a notably high incidence of landslides. The topographical wetness index exhibits an inverse correlation with landslide occurrences. The stream power index exhibits a positive correlation with the frequency of landslides. The interplay of slope, stream power index, aspect, and curvature has collectively contributed to the occurrence of landslides in the study area.